THE LOWER TOLUCA PUMICE: A CA. 21,700 YR B.P. PLINIAN ERUPTION OF NEVADO DE TOLUCA VOLCANO, MÉXICO - Capra L.; Carreras L.M.; Arce J.L.; Macías J.L. (My University, 2006)
Approximately 21,700 yr B.P., after a period of quiescence of ̃4800 yr, Nevado de Toluca volcano erupted, producing the Lower Toluca Pumice deposit. The activity generated a 24-km-high Plinian column that lasted ̃11-13 h and dispersed 2.3 km3 (0.8 km3 dense rock equivalent) of tephra toward the NE, blanketing the Lerma basin, an area occupied today by the city of Toluca, with up to 5 cm of ash. Subsequent eruptive pulses were sub-Plinian in style, accompanied by phreatomagmatic explosions that emplaced surge deposits. Finally, the column collapsed toward the NE with the emplacement of a pumice flow deposit. The high vesicularity of the pumice from the basal Plinian layer, up to 83% by volume, indicates that exsolution was dominantly magmatic, and that pressurization of the magma chamber was probably due to a magma mixing process. Evidence for this includes the compositional range of juvenile products (61-65 wt% SiO2), as well as the presence of two types of plagioclase, one in equilibrium and the other one with disequilibrium textures and reverse zoning. This suggests input of an andesitic liquid into the dacitic magma chamber. Based on the eruptive record, the most likely future eruptive activity at Nevado de Toluca volcano will be Plinian. Although quiet for more than 3250 yr, Plinian activity could occur after a long period of quiescence, and it could represent a hazard for the entire Toluca basin, where more than one million people live today. © 2006 Geological Society of America.
Keywords: NEVADO DE TOLUCA; PLINIAN ERUPTION; TRANS-MEXICAN VOLCANIC BELT